2014
DOI: 10.1590/0074-0276140315
|View full text |Cite
|
Sign up to set email alerts
|

High occurrence of Calodium hepaticum (syn. Capillaria hepatica) spurious infection in a village in the Atlantic Forest of southern Brazil

Abstract: Calodium hepaticum (syn. Capillaria hepatica) is a nematode of the Capillariidae family that infects rodents and other mammals. In Brazil, human spurious infections of C. hepaticum have been detected in indigenous or rural communities from the Amazon Basin, but not in the southern states of the country. Here, we report the highest occurrence (13.5% of 37 residents) of C. hepaticum human spurious infection detected in Brazil and the first record in a southern region, Guaraqueçaba. The finding is explained by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In addition, capybaras can serves as hosts of Capillaria hydrochoeri, adult worms are gastrointestinal parasites and eggs released along with host feces show distinct morphometric traits in comparison with C. hepaticum 33 . In spite of the fact that C. hepaticum eggs show morphometric differences according to different microenvironments (liver from different hosts or feces) 4,5,14,34 , we confirmed this species identification on the basis of morphological and morphometric determination of 100 eggs 5 . In Acre, it seems more likely that people get infected by eating paca meat 15 .…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…In addition, capybaras can serves as hosts of Capillaria hydrochoeri, adult worms are gastrointestinal parasites and eggs released along with host feces show distinct morphometric traits in comparison with C. hepaticum 33 . In spite of the fact that C. hepaticum eggs show morphometric differences according to different microenvironments (liver from different hosts or feces) 4,5,14,34 , we confirmed this species identification on the basis of morphological and morphometric determination of 100 eggs 5 . In Acre, it seems more likely that people get infected by eating paca meat 15 .…”
Section: Discussionsupporting
confidence: 66%
“…This eating behavior can pose a threat to these human populations. Previous studies have reported that individuals can develop C. hepaticum spurious infections by consuming raw or undercooked livers from wild hosts, both in Amazonian and Southern Brazilian communities [4][5][6]13,14 . In the present study, all the families reported eating whitelipped peccary, capybara (Hydrochoerus hydrochaeris) and lowland paca.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spurious infections occur due to ingestion of non-embryonated eggs, found on the ground or by eating the liver of mammals infected with C. hepaticum . About 135 cases of spurious infections were reported in literature; 94 of them occurred in Brazil, in the states of Amazonas , Minas Gerais , and Paraná 18 , 19 . Diagnoses took place mainly in indian tribes, due to the consumption of hunted animals, such as tapir ( Tapirus terrestris ), white-lipped peccary ( Tayasu pecari ), and red-faced spider monkey ( Ateles pasnicus ) 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%